THE CONCEPTS OF GOD, MAN, AND THE ENVIRONMENT IN ISLAM: IMPLICATIONS FOR ISLAMIC ARCHITECTURE - Omer, Spahic (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2012)
This paper discusses the concepts of God, man, and the natural environment, as well as some of their implications for Islamic architecture. The paper is divided into eight sections, (1) Introduction: what is Islamic architecture?, (2) Tawhid (God’s Oneness), (3) Islam and the role of man on earth, (4) Islam and the environment, (5) The importance of built environment, (6) Peaceful and sustainable coexistence between the environment, architecture and man, (7) The unique soul of Islamic architecture, and (8) Conclusion. The nature of the paper – its content, methodology, and conclusions –, is conceptual and philosophical, rather than empirical. The paper concludes that Islamic architecture is an architecture that through its multidimensionality embodies the message of Islam. It both facilitates the Muslims’ realization of the Islamic purpose and its divine principles on earth and promotes a lifestyle generated by such a philosophy and principles. At the core of Islamic architecture lies function with all of its dimensions: corporeal, cerebral and spiritual. The role of the form is an important one too, but only inasmuch as it supplements and enhances function. Keywords: Man, Islamic architecture, God, environment